Designing an Instrument to Conduct a Survey on Requirement Reuse Practices in Malaysia - Noraini Che Pa; Norhayati Md Ali; Noranis Mohd Aris; Rodziah Atan; Ainita Ban; Hazlina Hamdan; Mohamed Hazrat Ariffin (School of Industrial and System Engineering, Telkom University, 2019)
A set of questionnaire was designed to study the current state of requirement reuse practices in Malaysia. This paper describes the design of the survey on requirement reuse practice instrument, and the assessment of its reliability and validity. Cronbach’s Alpha test was used to check on its reliability and respondents’ feedback, to assess the level of understanding, the level of difficulty in responding and the level of relevancy to the subject area including the duration taken to complete the questionnaire. Results from the feedback suggested three main issues that need to be looked upon as a way to improve the instrument design. Future efforts will focus on improving the structure and contents of the questionnaire in order to achieve higher reliability and better number of responses to study on requirement reuse. Keywords—requirement reuse, requirement, engineering, software development, survey design